2021
DOI: 10.1111/jnc.15445
|View full text |Cite
|
Sign up to set email alerts
|

Proline‐arginine poly‐dipeptide encoded by the C9orf72 repeat expansion inhibits adenosine deaminase acting on RNA

Abstract: A GGGGCC hexanucleotide repeat expansion in the C9orf72 gene is linked to the pathogenesis of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) (C9‐ALS/FTD). Unconventional translation of the hexanucleotide repeat expansion generates five dipeptide repeat proteins (DPRs). The molecular mechanism underlying the DPR‐linked neurotoxicity is under investigation. In this study, using cell‐based models, we show that poly‐proline‐arginine DPR (poly‐PR), the most neurotoxic DPR in vitro, binds to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Furthermore, reduced ADAR2 activity is found in some familial ALS cases as well as in most sporadic ALS cases. The presence of Q/R site-unedited GluA2 due to downregulation of ADAR2 has been observed in motor neurons of patients with ALS carrying the FUS P525L mutation [144], and reduced ADAR2 activity due to ADAR2 mislocalization or binding with poly-PR and widespread reduction in RNA editing has been found in the motor neurons and iPSC-derived motor neurons of patients with ALS carrying C9orf72 with enhanced HRE [145,146].…”
Section: Dysregulation Of Rna Editing In Als Motor Neurons (Table 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, reduced ADAR2 activity is found in some familial ALS cases as well as in most sporadic ALS cases. The presence of Q/R site-unedited GluA2 due to downregulation of ADAR2 has been observed in motor neurons of patients with ALS carrying the FUS P525L mutation [144], and reduced ADAR2 activity due to ADAR2 mislocalization or binding with poly-PR and widespread reduction in RNA editing has been found in the motor neurons and iPSC-derived motor neurons of patients with ALS carrying C9orf72 with enhanced HRE [145,146].…”
Section: Dysregulation Of Rna Editing In Als Motor Neurons (Table 1)mentioning
confidence: 99%
“…Collectively, as RNA editing plays a pivotal role in brain aging and in the pathogenesis of sporadic ALS, as well as some forms of familial ALS, dysregulation of RNA editing might provide clues for the identification of biomarkers and serve as a potential therapeutic target for both brain aging and ALS (Table 1). Intron-derived circRNA is translated into toxic DPR proteins [93,145,146] Abbreviations: ALS-amyotrophic lateral sclerosis; ADAR2-adenosine deaminase acting on RNA2; TDP-43-transactive response DNA-binding protein of 43 kDa; FUS-fused in sarcoma; HRE-hexanucleotide repeat expansion; DPR-dipeptide repeat.…”
Section: Dysregulation Of Rna Editing In Als Motor Neurons (Table 1)mentioning
confidence: 99%
“…Furthermore, reduced ADAR2 activity due to the loss of nuclear ADAR2 rather than a decrease in ADAR2 expression was reported the cause of a widespread reduction in RNA editing with ADAR2 cytoplasmic mislocalization in the motor neurons and differentiated motor neurons, which were generated from iPSCs derived from ALS patients carrying C9ORF72 with enhanced hexanucleotide repeat expansion [122]. Moreover, it has been demonstrated that dipeptide repeat proteins derived from the hexanucleotide repeat expansion of C9ORF72 bind to ADAR1 and ADAR2, thereby inhibiting their RNA editing activity in vitro [123]. However, one study reported that all GluA2 was edited at the Q/R site in the motor neurons differentiated from iPSCs derived from ALS patients carrying C9ORF72 with enhanced hexanucleotide repeat expansion [124].…”
Section: Figurementioning
confidence: 99%
“…In various ALS models, poly(PR) is more toxic than poly(GR). 11 , 12 , 17 In addition, poly(PR) localizes mainly to the nucleolus, whereas poly(GR) is present in the cytoplasm and nucleolus and is often observed only in the cytoplasm, 18 , 19 , 20 , 21 resulting in different interactomes. 22 , 23 , 24 The difference in localization is confirmed for both short 20-repeat DPRs 19 and DPRs with more than 1000 repeats, which is a physiologically-relevant size.…”
Section: Introductionmentioning
confidence: 99%